INTEGRITAS DAN ETIKA TENAGA KESEHATAN DALAM PELAYANAN PUBLIK: STUDI KASUS DI RSUD X KOTA PALEMBANG - Muhammad Hafizh Syahputra; Natasya Dhea Karolin; Naiyla Atikha Syafitri; Hazirah Agustin; Shafira Amelia; Thalia Nova Fitri; Taufal Sen You; Riza Adelia Suryani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the application of integrity and ethics among health workers in public services at X Regional General Hospital in Palembang and to identify patients' perceptions of the quality of services provided. The study uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews with health workers and patients, which were then analyzed using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that integrity is understood as the harmony between values, words, and actions reflected in honesty, discipline, responsibility, transparency, and a focus on patient safety. Professional ethics are applied through compliance with professional standards, codes of ethics, and SOPs, as well as fair service without discrimination. Patients assessed that medical services were good in terms of attitude, communication, empathy, and speed of treatment. Obstacles were still found in the BPJS administrative process, which was considered more complex and time-consuming. Analysis based on public service theory and the SERVQUAL model shows that the dimensions of responsiveness, assurance, and empathy have been well fulfilled, while the aspects of reliability and tangibles in the administrative system still need to be improved. Strengthening a culture of integrity, improving the administrative system, and enhancing service coordination are important factors in improving the quality of public services and patient satisfaction